Linking multiple-channel information seeking and lifestyle among Chinese older adults: A moderation and mediation analysis - Qingrui Li; Yifang Wu; Xinshu Zhao (Digital Health)
Background Healthy lifestyle improvement of older Chinese adults has drawn a lot of attention due to an exceeding ageing population in mainland China. The current study aims to investigate the beneficial functions of the multi-channel health information seeking on elders’ lifestyle self-management. Objective We conducted a mediation analysis to test the association between multi-channel information seeking behavior and lifestyle self-management, which mediates by perceived self-management competence. Meanwhile, we also test the moderation effect of perceived self-management competence on lifestyle management with motivation for health promotion and prevention as the moderator. Methods To examine this mediation and moderation effects, we conducted a quota sampling online survey in mainland China from June 11 to October 12, 2023. The final sample size was 898 Chinese respondents aged 60 or above, with 54.5% male. Results Health information seeking using the mHealth app ( b p  = .03, 95% CI: [.005, .055]) and social media ( b p  = .06, 95% CI: [.031, .086]) is positively associated with lifestyle self-management through perceived self-management competence. While broadcast media ( b p  = .01, 95% CI: [−.015, .040]), print media ( b p  = .01, 95% CI: [−.015, .026]), and search engine ( b p  = .02, 95% CI: [−.006, .043]) show no significant impact on lifestyle management. Furthermore, health promotion and prevention motivation shows a positive moderation effect on perceived self-management competence and lifestyle management. Conclusions Our findings show evidence supporting a cognitive mechanism of moderated mediation that links seeking health information to improve LSM in older Chinese adults. It is essential for health self-education and health promotion among older Chinese adults.